2021
DOI: 10.32598/bcn.12.2.2378.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Quantitative Electroencephalography-Based Neurofeedback Therapy on Anxiety, Depression, and Emotion Regulation in People with Generalized Anxiety Disorder

Abstract: Introduction: Generalized Anxiety Disorder (GAD) is one of the most common anxiety disorders that has significant adverse effects on social functioning, occupational/academic performance, and daily living. This study aimed to evaluate the effect of Quantitative Electroencephalography (QEEG)-based Neurofeedback (NFB) therapy on anxiety, depression, and emotion regulation of people with GAD. Methods: This research is a quasi-experimental study with a pre-test/post-test/follow-up design and a control group. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Indeed, neurofeedback refers to an brain training changing the number of synapses between neurons through learning and conditioning (86) improving the voluntary regulation of specific brain regions (87). It was demonstrated to be effective in improving self-control (88)(89)(90)(91). Thus, such tools empower young people and may help them to improve their ability to cope with anger.…”
Section: Clinical and Preventive Implicationsmentioning
confidence: 99%
“…Indeed, neurofeedback refers to an brain training changing the number of synapses between neurons through learning and conditioning (86) improving the voluntary regulation of specific brain regions (87). It was demonstrated to be effective in improving self-control (88)(89)(90)(91). Thus, such tools empower young people and may help them to improve their ability to cope with anger.…”
Section: Clinical and Preventive Implicationsmentioning
confidence: 99%
“…An NFB treatment is an operant conditioning training program that aims to modify brain activity for therapeutic or performance-enhancing purposes (Budzynski et al, 2009;Gruzelier, 2014;Sitaram et al, 2017). NFB treatments have an experimental treatment status (Thibault and Raz, 2016), with ongoing research of their effects on disorders such as ADHD (Lubar et al, 1995;Simkin et al, 2014Simkin et al, , 2016, anxiety disorders (Hammond, 2006;Abdian et al, 2021), epilepsy (Egner and Sterman, 2006;Sterman and Egner, 2006;Morales-Quezada et al, 2019), and LDs (Fernández et al, 2003;Becerra et al, 2006;Breteler et al, 2010;Nazari et al, 2012;Martínez-Briones et al, 2021). Children with LD often exhibit an abnormally slower resting-state EEG than children with typical development, characterized by an excess of theta activity and a deficit of alpha activity (Chabot, 2001;Fernández et al, 2002;Fonseca et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another significant therapeutic approach for improving anxiety disorders is neurofeedback (Aghaziarati et al, 2023;Dinarvand et al, 2020). Neurophysiological research examining the relationship between electroencephalography, underlying thalamocortical brain mechanisms, and psychological states has shown that creating optimal oscillations and changes in brain wave rhythm and frequency through neurotherapeutic methods can induce optimal changes in psychological states, particularly in patients with anxiety disorders (Abdian et al, 2021;Banerjee & Argáez, 2017;Dinarvand et al, 2020;Ghayour-Kazemi et al, 2015;Gholizadeh & Abdollahi, 2017;Hosseini et al, 2022;Naeinian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%